Monocyte-derived exosomal periostin driven by histone lactylation contributes to retinal neovascularization - Wei Shen; Zheng Nie; Mengzhu Wang; Haorui Zhang; Yongxuan Liu; Huimin Zhu; Wen Zhou; Lin Zhang; Min Zhao; Hao Zeng; Mai Peng; Yukun Zhou; et al. (Proceedings of the National Academy of Sciences, 2025)
Exosomes are signaling messengers facilitating intercellular communication by delivering molecular cargo. Here, we observed increased levels of exosomal periostin (POSTN) in the blood plasma of patients with proliferative diabetic retinopathy (PDR). Monocytes contributed to elevated levels of exosomal POSTN, and deletion of Postn in myeloid cells reduced retinal neovascularization (RNV). Monocytes isolated from the blood of PDR patients or under high glucose conditions exhibited heightened glycolytic activity and elevated histone lactylation levels, particularly H4K8 lactylation (H4K8la). Knockout of hexokinase 2 ( Hk2 ) in myeloid cells led to reduced H4K8la and POSTN levels and inhibited RNV. Exogenous exosomal POSTN partially reversed the angiogenic defects caused by Postn or Hk2 deletion in myeloid cells. Mechanistically, exosomal POSTN stabilized hypoxia-inducible factor -1 alpha and upregulated the expression of angiogenic genes. Notably, treatment with metformin reduced RNV by decreasing monocyte glycolysis and lowering exosomal POSTN levels. In summary, these findings underscore the critical role of circulating exosomal POSTN in RNV and highlight its potential as a therapeutic target for angiogenic retinopathies.